2016
DOI: 10.4236/msa.2016.712065
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Acoustic Noise Correlation Technique for Passive Monitoring of Rails

Abstract: The work presented in this paper aims at investigating the ability of acoustic noise correlation technique for railway infrastructure health monitoring. The principle of this technique is based on impulse responses reconstruction by correlation of random noise propagated in the medium. Since wheel-rail interaction constitutes a source of such noise, correlation technique could be convenient for detection of rail defects using only passive sensors. Experiments have been carried out on a 2 m-long rail sample. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Theoretical and experimental studies in several areas [25][26][27][28], have shown that the active acoustic signal between two measurement points can be passively estimated from the time derivative of the correlation function of the signal recorded at those points.…”
Section: Passive Detection Methodsmentioning
confidence: 99%
“…Theoretical and experimental studies in several areas [25][26][27][28], have shown that the active acoustic signal between two measurement points can be passively estimated from the time derivative of the correlation function of the signal recorded at those points.…”
Section: Passive Detection Methodsmentioning
confidence: 99%
“…Passive ultrasonic sensing has gained much attention in several fields including underwater acoustics [1][2][3], seismology [4][5][6][7], seismic interferometry for dynamic identification of civil structure [6,[8][9][10][11][12][13], as well as SHM and NDT for defect detection [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. These applications stemmed from the seminal work of Lobkis and Weaver [28] who demonstrated that if a closed or open system is excited by a diffuse wave field (e.g.…”
Section: Introductionmentioning
confidence: 99%